2011
DOI: 10.1093/annonc/mdq758
|View full text |Cite
|
Sign up to set email alerts
|

Combination of hsa-miR-375 and hsa-miR-142-5p as a predictor for recurrence risk in gastric cancer patients following surgical resection

Abstract: these results are the first to indicate that the KRAS 3'UTR polymorphism may predict for cetuximab responsiveness in KRASwt mCRC patients, which warrants validation in other clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 33 publications
3
89
0
Order By: Relevance
“…Although several studies did not notice an upregulation of miR-375 in prostate carcinoma samples, various studies observed increased levels of this miRNA in prostate cancer serum samples (44,45). Publications confirm that miR-375 is downregulated in other cancer types such as cervical, lung, or head and neck carcinoma, as well as glioma (46)(47)(48)(49)(50) but upregulated in breast carcinoma (51).…”
Section: Discussionmentioning
confidence: 88%
“…Although several studies did not notice an upregulation of miR-375 in prostate carcinoma samples, various studies observed increased levels of this miRNA in prostate cancer serum samples (44,45). Publications confirm that miR-375 is downregulated in other cancer types such as cervical, lung, or head and neck carcinoma, as well as glioma (46)(47)(48)(49)(50) but upregulated in breast carcinoma (51).…”
Section: Discussionmentioning
confidence: 88%
“…Other genes involved in Wnt pathway were revealed as potential target of miR30a (Runx2, CDH1, Wnt5A) and miR-103 (Axin2) in expression profiling studies in gastric cancer [160] . Moreover, hsa-miR-375 upregulation and hsa-miR-142-5p downregulation have been indicated as predictor for recurrence risk in gastric cancer patients following surgical resection, probably by regulating several Wnt/ b-catenin target genes [162] . In Chinese patients with gastric cancer other miRNA genes that regulate Wnt/b-catenin target genes, such as miR-144, hsa-miR-148a and miR-193b were found downregulated [163][164][165] .…”
Section: Role Of Micrornas In Wnt/b-catenin Signaling In the Gastric mentioning
confidence: 99%
“…According to the United States' statistics released in 2010 the incidence rate of colon has decreased (2). Over the last decade, many studies have proposed various kinds of statistical methods to analyze gene expression patterns and identify new biomarkers for prognostic and/or predictive information in relation to human diseases (3,4). However, most of the early studies applied unsupervised approaches to data-mining and identification of differential gene expressed profiling of certain diseases, such as hierarchical clustering for class discovering, taking an unbiased approach to searching for subgroups in the data (5).…”
Section: Introductionmentioning
confidence: 99%